(untitled) (Clinics, 2016)
OBJECTIVES: Considering that changes in the maternal environment may result in changes in progeny, the aim of this study was to investigate the influence of sleep restriction during the last week of pregnancy on renal function and autonomic responses in male descendants at an adult age. METHODS: After confirmation of pregnancy, female Wistar rats were randomly assigned to either a control or a sleep restriction group. The sleep-restricted rats were subjected to sleep restriction using the multiple platforms method for over 20 hours per day between the 14th and 20th day of pregnancy. After delivery, the litters were limited to 6 offspring that were designated as offspring from control and offspring from sleep-restricted mothers. Indirect measurements of systolic blood pressure (BPi), renal plasma flow, glomerular filtration rate, glomerular area and number of glomeruli per field were evaluated at three months of age. Direct measurements of cardiovascular function (heart rate and mean arterial pressure), cardiac sympathetic tone, cardiac parasympathetic tone, and baroreflex sensitivity were evaluated at four months of age. RESULTS: The sleep-restricted offspring presented increases in BPi, glomerular filtration rate and glomerular area compared with the control offspring. The sleep-restricted offspring also showed higher basal heart rate, increased mean arterial pressure, increased sympathetic cardiac tone, decreased parasympathetic cardiac tone and reduced baroreflex sensitivity. CONCLUSIONS: Our data suggest that reductions in sleep during the last week of pregnancy lead to alterations in cardiovascular autonomic regulation and renal morpho-functional changes in offspring, triggering increases in blood pressure.